Monitoring of Heparin and Low Molecular Weight Heparin with Capillary and Venous Whole Blood - Harenberg, J; Giese, Ch; Dempfle, C E; Stehle, G; Heene, D L (Thrombosis and Haemostasis, 1988)
A method for determination of antifactor Xa-like activity in capillary whole blood obtained from the fingertip is described, which employs the Heptest coagulation assay. Values obtained with capillary whole blood are compared to values of corresponding plasma and venous whole blood samples. Normal values in plasma, venous whole blood, and capillary blood from the fingertip were 17.1 ± 2.1, 10.0 ± 1.3 and 10.4 ± 1.3 sec, respectively. The intraindividual coefficients of variations range from 0.4 to 1.8% in all assays. The day to day coefficient of variation of normal values ranged between 0.8 and 2.0% for all assays. The within assay coefficients of variation ranged from 3.0 to 7.7% for whole blood samples and from 1.5 to 2.2% for plasma samples after addition of no, 0.2 or 1.0 units of normal or LMW heparin to the samples. After administration of heparin or LMW heparin in healthy persons the coagulation values of the different coagulation assay systems displayed coefficients of correlation betweell r = 0.87 and r = 0.95. Correlation coefficients between the coagulation tests and the S 2222 chromogenic substrate method ranged from r = 0.77 to r = 0.92. In patients, who received LMW heparin for prophylaxis of thromboembolism the coagulation assay correlated between r = 0.78 and 0.92. The coagulation assays and the S 2222 method displayed coefficients of correlation between r = 0.74 and r = 0.83. The data indicate that Heptest sensitively measures antifactor Xa-like activity in capillary whole blood as well as venous whole blood samples containing low quantities of heparin or LMW heparin.
Keywords: Heparin; Low molecular weight heparin; Coagulation assays; Chromogenic substrate assays